Ekosystem biznesu jako platforma relacji kooperacyjnych przedsiębiorstw - Cygler, Joanna (Business Ecosystem as a Platform for Co-opetitive Relations of Enterprises, 2008)
Co-opetition (simultaneous competition and co-operation between competitors) can occur not only at the corporate and sector levels, but also at a business ecosystem. Business ecosystem is a combination of several organizations from different industries forming a strategic community of interests and values. Co-opetition can be concluded both at intra and inter business ecosystem levels. Co-opetitive relations are different depending on the ecosystem life stage. Moreover, there is a strong correlation between an inclination of enterprises to create co-opetitive relations with their competitors and overall condition of the business ecosystem measured by the productivity, robustness, and niche creation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 47-57